2009
DOI: 10.1111/j.1600-6143.2008.02519.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Specific Causes of Kidney Allograft Loss

Abstract: The causes of kidney allograft loss remain unclear. Herein we investigated these causes in 1317 conventional kidney recipients. The cause of graft loss was determined by reviewing clinical and histologic information the latter available in 98% of cases. During 50.3 ± 32.6 months of follow-up, 330 grafts were lost (25.0%), 138 (10.4%) due to death with function, 39 (2.9%) due to primary nonfunction and 153 (11.6%) due to graft failure censored for death. The latter group was subdivided by cause into: glomerular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
537
7
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 726 publications
(579 citation statements)
references
References 30 publications
23
537
7
12
Order By: Relevance
“…In 2009, El-Zoghby et al differentiated the reasons for chronic transplant loss. These authors identified CAMR as a main cause in adults [1]. The same has been shown in children [51].…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 59%
See 1 more Smart Citation
“…In 2009, El-Zoghby et al differentiated the reasons for chronic transplant loss. These authors identified CAMR as a main cause in adults [1]. The same has been shown in children [51].…”
Section: Chronic Antibody-mediated Rejection (Camr)mentioning
confidence: 59%
“…The last decades have been very successful regarding the prevention and treatment of acute cellular rejection. However, chronic antibodymediated rejection (CAMR) remains a leading cause of the late loss of kidney transplants in adults [1]. The prevalence of CAMR could even be higher in pediatric nephrology.…”
Section: Introductionmentioning
confidence: 99%
“…After censoring for death, however, similar findings remain, and it is likely that chronic alloimmune damage is a major cause of graft loss in this cohort as reported elsewhere. [28][29][30][31][32] Finally, HLA typing methods have evolved, such that the HLA antigens identified in one donor may be more fully resolved than the other donor or in the recipient. 33 Where this resolution discrepancy existed, we classified the antigens as equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…IF/TA is detectable in about 40% of kidney allografts at 3-6 months (6,7) and increases to about 65% at 2 years (8). IF/TA is a non-specific lesion induced by various immune and non-immune injuries to the graft (9,10) and an independent risk factor for late graft loss, particularly in grafts from expanded criteria donors, irrespective of whether a specific disease was diagnosed in the allograft or not (11)(12)(13)(14)(15). However, ''IF/TA'' should only be diagnosed if the underlying etiology of fibrosis and tubular atrophy is not clear (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, ''IF/TA'' should only be diagnosed if the underlying etiology of fibrosis and tubular atrophy is not clear (5). With protocol biopsies and detailed clinical information a cause of graft dysfunction can be recognized in most cases, with the majority being due to chronic rejection (9,10,12,16). Therefore, within this review we will use not use the term IF/TA but rather discuss renal fibrosis in general given that there is little to no evidence that the allograft fibrosis as part of IF/TA or any other allograft pathology differs significantly from the fibrosis observed in other progressive diseases of native kidneys.…”
Section: Introductionmentioning
confidence: 99%